Gambaran Kemampuan Pedagogical Content Knowledge Guru Ipa Kelas Vii Smp Negeri Se-Kabupaten Sukoharjo Dalam Menggunakan Kurikulum 2013 Tahun Ajaran 2016/2017 - Chotimah, Khusnul; , Dra. Hariyatmi, M. Si (2017)
Teachers hold in determining process and learning outcomes of learnes. Pedagogical Content Knowledge (PCK) is needed for teachers to carry out the study. The purpose of the study is to find out the PCK capability of science teachers at seventh grade junior high school in Sukoharjo in applying curriculum 2013 academic year 2016/2017. The research is descriptive with documentation lesson plan. The population was all science teachers at seventh grade junior high school in Sukoharjo with curriculum 2013. Samples were taken by random sampling which one teacher in each school with totaling 13 teachers. There were 52 lesson plan that identified by taking 4 lesson plan from each teacher. The results show that CK capability is 41,79% (medium) and the PK capability is 65,81% (good). PCK capability from 14 sub aspects that identified, there were 10 sub aspects that good and 4 sub aspects still low. The highest capability was used strategies suitable grade of learners (84,77%) and the lowest was arranging content suitable curriculum (41,54%). The PCK capability of the science teachers at seventh grade junior high school in Sukoharjo in applying curriculum 2013 academic year 2016/2017 can be concluded is good (66,02%).